Gastric infarction following gastric bypass surgery - Do, Patrick H (J Radiol Case Rep, 2016)
Gastric infarction is an extremely rare occurrence owing to the stomach’s extensive vascular supply. We report an unusual case of gastric infarction following gastric bypass surgery. We describe the imaging findings and discuss possible causes of this condition.